Continuous auditing: A new instrument in the CFO’s toolbox - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2017)
In the past decade, rapid technological developments have led to the widespread adoption of enterprise resource planning systems. These ERP platforms not only allow different functional areas of a business to share data, but also enable businesses to generate financial information in real time.Such developments have fundamentally altered how businesses operate, and present both challenges and opportunities for CFOs and auditors.That’s because traditional audit methods have, to a significant extent, not kept up with these developments. Many audit procedures that are used today remain manual in nature, and are often costly in terms of both time and money. To a large degree, it is as a result of these associated costs that audits are only conducted on an annual basis today.One emerging automation concept/technology that is gaining prominence in audit is the continuous audit.